(N}EDRIN SO^INENIQ DLQ FORTEPIONO TOM (B2s (NFORTEPIANOs - (N}EDRIN(B.(Nr(B. (Nk(B.s ((NmOSKWAs (NmUZYKAs, 2007)
(NwO WTOROJ TOM SO^INENIJ DLQ FORTEPIANO WYDA@]EGOSQ OTE^ESTWENNOGO KOMPOZITORA r(B.(Nk(B. (N}EDRINA WO[LI POPULQRNYE PXESY pO\MA `MARSKA(B.s
Keywords: (NFORTEPIANOs